Crystallographic Studies of Chemically Modified Nucleic Acids: A Backward Glance - Egli, Martin (2010)
Chemically modified nucleic acids (CNAs) are widely explored as antisense oligonucleotide or small interfering RNA (siRNA) candidates for therapeutic applications. CNAs are also of interest in diagnostics, high-throughput genomics and target validation, nanotechnology and as model systems in investigations directed at a better understanding of the etiology of nucleic acid structure as well as the physical-chemical and pairing properties of DNA and RNA and for probing protein-nucleic acid interactions. In this article we review research conducted by our laboratory over the past two decades with a focus on crystal structure analyses of CNAs and artificial pairing systems. We highlight key insights into issues ranging from conformational distortions as a consequence of modification to the modulation of pairing strength and RNA affinity by stereoelectronic effects and hydration. Although crystal structures have only been determined for a subset of the large number of modifications that were synthesized and analyzed in the oligonucleotide context to date, they have yielded guiding principles for the design of new analogs with tailormade properties, including pairing specificity, nuclease resistance and cellular uptake. And, perhaps less obviously, crystallographic studies of CNAs and synthetic pairing systems have shed light on fundamental aspects of DNA and RNA structure and function that would not have been disclosed by investigations solely focused on the natural nucleic acids.